Borehole measurements in geothermal wells: Why one should measure and know certain parameters - Bauer, Wolfgang (EAGE/BVG/FKPE Joint Workshop on Borehole Geophysics and Geothermal Energy, 2019)
Geothermal projects are often characterized by high cost pressure and a focused on the implementation of a single project. As a result, a comprehensive borehole measurement program is often dispensed with and only a minimum of measurements are performed. The purpose of this talk is to clarify the importance of borehole measurements with regard to a comprehensive understanding of the subsurface and to explain the necessity of certain measurement methods by means of a proposal for a measurement program.
CRIS-Team Scopus Importer:2021-04-20